2019
DOI: 10.1155/2019/5196028
|View full text |Cite
|
Sign up to set email alerts
|

mTORC2 Regulates Lipogenic Gene Expression through PPARγ to Control Lipid Synthesis in Bovine Mammary Epithelial Cells

Abstract: The mechanistic target of rapamycin complex 2 (mTORC2) primarily functions as an effector of insulin/PI3K signaling to regulate cell proliferation and is associated with cell metabolism. However, the function of mTORC2 in lipid metabolism is not well understood. In the present study, mTORC2 was inactivated by the ATP-competitive mTOR inhibitor AZD8055 or shRNA targeting RICTOR in primary bovine mammary epithelial cells (pBMECs). MTT assay was performed to examine the effect of AZD8055 on cell proliferation. EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This phenotype is partially rescued by overexpressing recombinant ACLY and completely rescued by overexpressing the phospho-mimetic construct ACLY-S455D (Calejman et al, 2020). A recent study using a non-adipocyte model (primary bovine mammary epithelial cells) also showed blocked PPARg2 expression when Rictor was knocked down by short hairpin RNA (shRNA) (Guo et al, 2019). Consistent with the brown and white preadipocyte differentiation models showing different requirements for mTORC2 (i.e., Rictor is not required for PPARg2 mRNA induction here), overexpressing ACLY-S455D did not rescue gene expression and lipid accumulation defects in the Rictor-deficient subcutaneous white preadipocytes in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype is partially rescued by overexpressing recombinant ACLY and completely rescued by overexpressing the phospho-mimetic construct ACLY-S455D (Calejman et al, 2020). A recent study using a non-adipocyte model (primary bovine mammary epithelial cells) also showed blocked PPARg2 expression when Rictor was knocked down by short hairpin RNA (shRNA) (Guo et al, 2019). Consistent with the brown and white preadipocyte differentiation models showing different requirements for mTORC2 (i.e., Rictor is not required for PPARg2 mRNA induction here), overexpressing ACLY-S455D did not rescue gene expression and lipid accumulation defects in the Rictor-deficient subcutaneous white preadipocytes in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In mature white adipocytes, the mechanistic target of rapamycin complex 2 (mTORC2) regulates glucose uptake and de novo lipogenesis (DNL) in vivo in part through regulating the carbohydrate response element binding protein (ChREBP) transcription factor ( Guo et al, 2019 ; Guri et al, 2017 ; Jung et al, 2019 ; Tang et al, 2016 ). In humans, a positive correlation between DNL in SWAT and systemic insulin sensitivity has been shown ( Eissing et al, 2013 ; Roberts et al, 2009 ; Smith and Kahn, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The PPARγ has been the most studied in dairy cows. In monogastrics this PPAR isotype is a pivotal player in adipogenesis and insulin sensitivity, but in dairy cows it has been specifically studied for its role in modulating milk fat synthesis [248][249][250], its involvement in the mTOR pathway, particularly mTORC2 [251], and its anti-inflammatory role [4,5]. All PPAR isotypes play a role in improving reproductive parameters of dairy cows, such as the mitigation of endometritis [252], contribution to folliculogenesis [253], reproductive hormone synthesis [253], and the development of embryos [254].…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%
“…Non-ruminant studies revealed that the mTOR pathway could regulate lipid synthesis by integrating various molecular signals culminating in the activation of adipogenesis/lipogenesis through SREBF1 and PPARG [ 26 , 27 , 28 , 29 ]. mTOR is essential for regulating SREBF1 at both transcriptional and post-translational levels [ 30 , 31 , 32 ], and mTORC2 can control lipid synthesis in BMECs by regulating the lipogenic gene expression through PPARG in ruminants [ 33 ]. In this study, the downregulation of mTOR at the mRNA level, as well as SREBF1 and PPARG , indicated a strong mechanistic link, whereby PER2 downregulated SREBF1 and PPARG through mTOR .…”
Section: Discussionmentioning
confidence: 99%